Kamel Khalil Al-Asaad and his political role in Lebanon 1908 -1924 - Al-Waeli, Dr. Ali Hussein Naeem Al-Waeli (Thi Qar Arts Journal, 2022)
Researchers in history dealt with Jabal Amel and its various religious and political personalities with study and analysis, but it did not single out a specific study of an important (Amili) personality that had a clear impact on the history of Lebanon in general, and the history of Jabal Amel in particular, which is the personality of Kamel Khalil Al-Asaad, so the title Research (Kamel Khalil Al-Asaad and his political role in Lebanon 1908-1924). Being the first global leader throughout the first quarter of the last century, especially since he is a descendant of an ancient Arab family that ruled southern Lebanon for a long period of time, as he experienced the Ottoman Empire, the Arab government in Damascus and the French mandate over Lebanon, and contributed to the events of that stage.